PSYCHOLOGICAL APPROACH TO SPEECH DEVELOPMENT OF PRE-SCHOOL CHILDREN - Tursunova Khumora Nodirovna (Journals Park Publishing, 2022)
This article talks about the development of preschool children's speech, the use of unique methods in the process of education, approaching pedagogical psychology.
Keywords: Children's vocabulary, speech culture, Situational, ideological spirit, speech skills